The localisation of the apical Par/Cdc42 polarity module is specifically affected in microvillus inclusion disease. (8th December 2015) - Michaux, Grégoire; Massey‐Harroche, Dominique; Nicolle, Ophélie; Rabant, Marion; Brousse, Nicole; Goulet, Olivier; Le Bivic, André; Ruemmele, Frank M.
Short Communication: Myo5B is required for the correct localisation of the apical Par/Cdc42 module in intestinal cells. The loss of Myo5B in Microvillus Inclusion Disease (MVID) or in cultured cells induces the conversion of intracellular or basal membranes into apical‐like membranes forming microvilli while the apical membrane presents a microvillus atrophy. The localisation of the apical Par/Cdc42 module is strictly correlated with the formation and maintenance of microvilli. Abstract : Background information: Microvillus inclusion disease (MVID) is a genetic disorder affecting intestinal absorption. It is caused by mutations in MYO5B or syntaxin 3 ( STX3 ) affecting apical membrane trafficking. Morphologically, MVID is characterised by a depletion of apical microvilli and the formation of microvillus inclusions inside the cells, suggesting a loss of polarity. To investigate this hypothesis, we examined the location of essential apical polarity determinants in five MVID patients. Results: We found that the polarity determinants Cdc42, Par6B, PKCζ/ι and the structural proteins ezrin and phospho‐ezrin were lost from the apical membrane and accumulated either in the cytoplasm or on the basal side of enterocytes in patients, which suggests an inversion of cell polarity. Moreover, microvilli‐like structures were observed at the basal side as per electron microscopy analysis. We next performed Myo5B depletion in three dimensional grown human Caco2 cells forming cysts and found a direct link between the loss of Myo5B and the mislocalisation of the same apical proteins; furthermore, we observed that a majority of cysts displayed an inverted polarity phenotype as seen in some patients. Finally, we found that this loss of polarity was specific for MVID: tissue samples of patients with Myo5B‐independent absorption disorders showed normal polarity but we identified Cdc42 as a potentially essential biomarker for trichohepatoenteric syndrome. Conclusion: Our findings indicate that the loss of Myo5B induces a strong loss of enterocyte polarity, potentially leading to polarity inversion. Significance: Our results show that polarity determinants could be useful markers to help establishing a diagnosis in patients. Furthermore, they could be used to characterise other rare intestinal absorption diseases.